Microwave-assisted surface attachment of aluminium ions on in situ diluted titanium-doped hematite photoanodes for efficient photoelectrochemical water-splitting. Issue 12 (1st June 2022) - Hwang, Jun Beom; Dhandole, Love Kumar; Anushkkaran, Periyasamy; Chae, Weon-Sik; Choi, Sun Hee; Lee, Hyun Hwi; Jang, Jum Suk
Abstract : Al/Ti co-doping was performed through an effective microwave-assisted surface attachment method. The synergistic effect of Al/Ti co-doping and an Al2 O3 passivation layer significantly boosts the PEC performance in the Al(5 mM)/Ti(4%):Fe2 O3 photoanode. Abstract : In this work, we introduce in situ diluted (ISD) hydrothermal synthesis of a titanium-doped Fe2 O3 photoanode and suggest a novel microwave-assisted surface attachment (MASA) method for fabricating an aluminium–titanium co-doped photoanode. The charge-carrier density of a hematite photoanode increases with Ti 4+ doping, which offers lower bulk resistance. Through MASA treatment, Al 3+ ions can be attached homogeneously on the surface of a Ti–FeOOH film from aqueous aluminium chloride. The charge recombination is weaker after the successful diffusion of Al 3+ and partial formation of self-induced Al2 O3, which acts as a surface passivation layer. The synergistic interaction of Al co-doping and surface passivation cathodically shifts the onset potential by 120 mV and enhances the photocurrent density to 1.32 mA cm −2 (1.23 V vs. RHE). MASA treatment not only improves the bulk characteristics of the photoanode but also enhances the surface injection efficiency which promotes water-splitting. The charge-transfer mechanism for the prepared photoanodes was also studied extensively.